2014
DOI: 10.1111/1756-185x.12338
|View full text |Cite
|
Sign up to set email alerts
|

Comparing female‐based contraceptive methods in patients with systemic lupus erythematosus, rheumatoid arthritis and a healthy population

Abstract: Aim: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that is 10 times more prevalent in women, particularly those of reproductive age. The varying effects of pregnancy on SLE and the differences between available SLE treatments make pregnancy timing and contraceptive methods significant. We aimed to determine the contraceptive methods used by SLE patients in the north-west part of Turkey, and compared them with those used by rheumatoid arthritis (RA) patients and healthy controls. Method:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…These findings on contraceptive prevalence were consistent with the findings of a cross‐sectional study among SLE patients in Finland where contraceptive use was 59% in SLE patients compared to 77% in the general population . However, our results are in contrast to Dalkilic et al . reporting contraceptive usage of 80%, 79% and 81%, respectively in SLE, RA and a healthy population in Turkey.…”
Section: Discussionsupporting
confidence: 92%
“…These findings on contraceptive prevalence were consistent with the findings of a cross‐sectional study among SLE patients in Finland where contraceptive use was 59% in SLE patients compared to 77% in the general population . However, our results are in contrast to Dalkilic et al . reporting contraceptive usage of 80%, 79% and 81%, respectively in SLE, RA and a healthy population in Turkey.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 35.2% of the patients with SLE received contraceptive consultations in the last year which shows a relatively lower rate compared to other studies ( 8 , 9 , 15 , 16 ). A study in Brazil found that among 85 women with SLE, 53% did not use any contraceptive method but 22% used condoms, 11% used combined oral contraceptives and 7% used hormone injections ( 9 ).…”
Section: Discussioncontrasting
confidence: 74%
“…A study in Brazil found that among 85 women with SLE, 53% did not use any contraceptive method but 22% used condoms, 11% used combined oral contraceptives and 7% used hormone injections ( 9 ). In another study in Turkey, 20.3% of SLE patients did not use any contraceptive methods, but using withdrawal and condom were found to be more common (withdrawal 32.7%, condom 28.3%) ( 16 ). According to Cravioto et al discontinuation rate for different methods of contraception is significantly different; 35% in OCP, 55% in progestin-only pills (POP), and 29% in IUD ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent clinical audit of sexually active women with rheumatologic conditions including RA found that only 57% of women on known teratogenic DMARDs were using effective contraception despite receiving specialist rheumatology care at a large teaching hospital [49]. A hospital-based study in Turkey also highlighted suboptimal contraceptive use among female patients with RA [50]. Appropriate education and support should also be made available outside the clinical setting as information seeking may not coincide with the timing of clinical consultations.…”
Section: Discussionmentioning
confidence: 99%